2018
DOI: 10.1136/bmjopen-2018-023749
|View full text |Cite
|
Sign up to set email alerts
|

Team talk and team decision processes: a qualitative discourse analytical approach to 10 real-life medical emergency team encounters

Abstract: ObjectivesExplore the function of three specific modes of talk (discourse types) in decision-making processes.DesignTen real-life admissions of patients with critical illness were audio/video recorded and transcribed. Activity-type analysis (a qualitative discourse analytical method) was applied.SettingInterdisciplinary emergency teams admitting patients with critical illness in a Norwegian university hospital emergency department (ED).ParticipantsAll emergency teams consisted of at least two internal medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Discourse analytical methods have also been utilized on other material in health services research, e.g. on recorded conversations between health care workers in different settings [ 43 ] and on interviews with clinicians [ 44 ]. It has, however, been suggested that discourse analysis is an underutilized methodology within health care system research [ 45 ], and a search in PubMed performed in September 2019, using the phrase “discharge summary discourse analysis” did not return any results.…”
Section: Discussionmentioning
confidence: 99%
“…Discourse analytical methods have also been utilized on other material in health services research, e.g. on recorded conversations between health care workers in different settings [ 43 ] and on interviews with clinicians [ 44 ]. It has, however, been suggested that discourse analysis is an underutilized methodology within health care system research [ 45 ], and a search in PubMed performed in September 2019, using the phrase “discharge summary discourse analysis” did not return any results.…”
Section: Discussionmentioning
confidence: 99%
“…These elements gave nurse managers the strength to go on as leaders. In addition, they wanted to be offered continuous support in different forms, both administrative and emotional, along with proper education and training throughout their time as leaders (Gundrosen, Thomassen, Wisborg, & Aadahl, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This key‐element label was attributed to 89 sources (Abramson & Mizrahi, 2003; Ambrose‐Miller & Ashcroft, 2016; Andermo et al, 2015; Anquinet et al, 2015; Baggs, 1994; Baggs et al, 2007; Baggs & Schmitt, 1995; Bajwa et al, 2020; Bartholdson et al, 2021; Bentovim & Gilmour, 1981; Berg et al, 2020. ; Bokhour, 2006; Borrett & Gould, 2021; Botes, 2000; Briggs, 1999; Brooks et al, 2017; Bunch, 2000; Caenepeel & Jobin, 2005; Cook et al, 2001; Coombs, 2003, 2014; Coombs & Ersser, 2004; Cranley et al, 2022; de Casterlé et al, 2006; Dekussche, 2005; Dimech et al, 2021; Duner, 2013; Durand et al, 2022; Ervin et al, 2018; Faith & Chidwick, 2009; Fein et al, 2016; Fiddick et al, 2020; Firn et al, 2020; Forbes et al, 2020; Forsgärde et al, 2021; Fox & Comeau‐Vallée, 2020; Fratianne et al, 1992; Friedman, 2020; Gair & Hartery, 2001; Geist & Chandler, 1984; Grafham et al, 2004; Greenhalgh et al, 2008; Gundrosen et al, 2018; Hagoel et al, 2011; Haines et al, 2018; Heath et al, 2016; Heerschap et al, 2019; Helzer et al, 2020; Ho et al, 2005; Husson, 2011; Jensen et al, 2013; Johal & Danbury, 2021; Jordan, 1982; Joseph & Conrad, 1989; Kane, 1975; Kayser & Kaplan, 2020; Kilpatrick...…”
Section: Resultsmentioning
confidence: 99%